2020
DOI: 10.1093/europace/euaa162.248
|View full text |Cite
|
Sign up to set email alerts
|

1319Local impedance on a force sensing catheter predicts volumetric lesion temperature changes

Abstract: Funding Acknowledgements Study was funded by Boston Scientific The effective delivery of RF energy is dependent on transmural tissue heating, with irreversible tissue necrosis occurring at a tissue temperature ≥ 50°C.  While multi-input lesion indexing algorithms can provide some value in predicting lesion durability, no clinically available metric measures tissue heating under the endocardial surface.  Temperature measured from the catheter at the tissue surface is a surrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…The LI continued to decrease under the 30 g/50 W, 50 g/50 W, and 50 g/40 W ablation settings, which indicated that the local tissue temperature continued to increase because the LI drop reflects the tissue temperature. 13 Finally steam pops occurred under during the 50 W ablation. Steam pops did not occur during the 40 W ablation in our experiment, but a longer ablation duration might have triggered a steam pop even if the ablation power was 40 W. The value of the LI might be useful to predict steam pops.…”
Section: Proportion Of Achieving An LI Drop At the Plateau Level And Incidence Of Steam Popsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LI continued to decrease under the 30 g/50 W, 50 g/50 W, and 50 g/40 W ablation settings, which indicated that the local tissue temperature continued to increase because the LI drop reflects the tissue temperature. 13 Finally steam pops occurred under during the 50 W ablation. Steam pops did not occur during the 40 W ablation in our experiment, but a longer ablation duration might have triggered a steam pop even if the ablation power was 40 W. The value of the LI might be useful to predict steam pops.…”
Section: Proportion Of Achieving An LI Drop At the Plateau Level And Incidence Of Steam Popsmentioning
confidence: 99%
“…Kara et al reported that the LI drop closely reflected the tissue temperature in an in-vitro porcine experiment. 13 The tissue temperature would be increasing under a higher CF or higher ablation power and the LI drop was be less likely to reach the plateau level.…”
Section: Proportion Of Achieving An LI Drop At the Plateau Level And Incidence Of Steam Popsmentioning
confidence: 99%
“…This catheter has 3 microelectrodes incorporated into the distal tip, and a more precise LI would be detected with these microelectrodes. Since the LI would be changed by tissue contact and temperature, this parameter allows us to speculate about the CF and tissue temperature during the RF application [11] . In addition, both LI-and CF-sensing ablation catheters (INTELLANAV STABLEPOINT Boston Scientific, Maple Grove, MN, USA: STABLEPOINT) have recently become available, and they will contribute to additional improvement in the quality of RFCA.…”
Section: Introductionmentioning
confidence: 99%
“…A local potential field is generated by driving a non-stimulatory current between a distal and a more proximal catheter electrode; proximity to physical structures such as myocardium causes distortions in this local field which can be measured with one or more intermediate electrodes, allowing derivation of a LI value 4 . Bench work has shown that during RF application, LI drop dynamically follows the rate of intramural temperature rise (Figure 1) 5 . The resulting tissue feedback can potentially allow operators to individualize each RF application, and several groups have already reported on their clinical experience (Table 1) with a LI-sensing catheter.…”
mentioning
confidence: 99%